Amino-modified graphene oxide adsorption material for efficiently treating hexavalent chromium and preparation method of amino-modified graphene oxide adsorption material
By grafting 4-amino-3-nitrogen-5-mercapto-1,2,4-triazacrol onto graphene oxide, an efficient amino-modified graphene oxide adsorption material (GO/ATA) was prepared, which solved the problems of high cost and low adsorption capacity of removing hexavalent chromium in water in the prior art, and achieved efficient, economical and environmentally friendly Cr(VI) removal effect.
Patent Information
- Application Number
- CN202411598693.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art has problems such as high cost, high energy consumption, and unstable treatment effect when removing hexavalent chromium (Cr(VI) in water, and graphene oxide (GO) itself has limited adsorption capacity to Cr(VI).
4-amino-3-nitrinitride-5-mercapto-1,2,4-triazacroton (AHMT) was grafted onto graphene oxide (GO) by a two-step method, and an amino-modified graphene oxide adsorption material (GO/ATA) was prepared to improve its adsorption performance on Cr(VI).
GO/ATA adsorption materials exhibit extremely high Cr(VI) adsorption capacity, excellent chemical stability and cycling performance, are suitable for large-scale applications, and meet safety and environmental standards.
Smart Images

Figure CN119608115A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chromium adsorption materials, and in particular to an amino-modified graphene oxide adsorption material for efficiently treating hexavalent chromium and a preparation method thereof. Background Art
[0002] Chromium (Cr) is a heavy metal pollutant widely present in industrial wastewater, especially its hexavalent form, which poses a serious threat to human health and environmental safety. Cr(VI) is highly toxic and carcinogenic, and long-term exposure or ingestion may cause lung cancer, nasopharyngeal cancer, skin ulcers and other diseases. Therefore, efficient removal of Cr(VI) from wastewater has become an important task in the field of environmental protection and sewage treatment.
[0003] At present, traditional Cr(VI) removal methods mainly include chemical precipitation, ion exchange and biological reduction. However, these methods have various problems. For example, chemical precipitation requires a high chemical dosage and a long reaction time to achieve a good removal effect, and the large amount of precipitate produced needs further treatment. Although ion exchange has high selectivity and removal efficiency, it has high energy consumption and cost. The biological reduction method is limited by the selection of bacterial strains and operating conditions, and the treatment effect is unstable.
[0004] Therefore, it is of great significance to develop a new and efficient adsorption material for removing Cr(VI) from water. Graphene oxide (GO), as a two-dimensional material with a large number of functional groups and a high specific surface area, is widely used in the adsorption and catalytic degradation of environmental pollutants. However, the adsorption capacity of GO itself for Cr(VI) is limited, so further modification is needed to improve its adsorption performance.
[0005] Therefore, the present invention aims at the problem of Cr(VI) pollution, and adopts a two-step method to graft 4-amino-3-azino-5-thiol-1,2,4-triazole (AHMT) onto GO to synthesize the amino-functionalized adsorbent material GO / ATA. The purpose is to improve the adsorption performance and selectivity of the adsorbent material, and provide an efficient, economical and environmentally friendly Cr(VI) removal technology for the wastewater treatment field. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide an amino-modified graphene oxide adsorbent material (GO / ATA) for efficiently treating hexavalent chromium and a preparation method thereof, wherein the adsorbent material has excellent hexavalent chromium adsorption performance, good chemical stability and cycle performance, and great application value.
[0007] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing an amino-modified graphene oxide adsorption material for efficiently treating hexavalent chromium is provided, comprising the following steps:
[0008] (1) adding 4-amino-3-azino-5-mercapto-1,2,4-triazole and terephthalaldehyde to dimethyl sulfoxide, stirring and mixing, then adding 3-aminopropyltriethoxysilane ethanol solution and stirring to react, and then cooling, filtering, washing and drying in sequence to obtain ATA;
[0009] (2) dissolving the ATA obtained in step (1) in dimethyl sulfoxide to obtain an ATA solution;
[0010] (3) dispersing graphene oxide in water, adding the ATA solution obtained in step (2), stirring overnight after ultrasonic treatment, and then filtering, washing and vacuum freeze-drying in sequence to obtain an amino-modified graphene oxide adsorbent material that is efficient in treating hexavalent chromium.
[0011] Furthermore, in step (1), the 3-aminopropyltriethoxysilane ethanol solution is prepared by mixing 3-aminopropyltriethoxysilane and ethanol in a ratio of 1:1.
[0012] Furthermore, in step (1), the mass volume ratio of the 4-amino-3-azino-5-mercapto-1,2,4-triazole, terephthalaldehyde, dimethyl sulfoxide and 3-aminopropyltriethoxysilane ethanol solution is 0.4-0.7 g: 0.4-0.7 g: 120-180 mL: 2-4 mL.
[0013] Furthermore, in step (1), the reaction is stirred at 50-70° C. for 10-15 h.
[0014] Furthermore, in step (1), drying is performed at 70-90° C. for 10-15 hours.
[0015] Furthermore, in step (2), the mass volume ratio of ATA and dimethyl sulfoxide is 1:1.
[0016] Furthermore, in step (3), the mass volume ratio of the graphene oxide, water and ATA solution is 0.1-0.3 g: 20-40 mL: 8-12 mL.
[0017] Furthermore, in step (3), stirring is carried out at 25° C. overnight.
[0018] Further, in step (3), vacuum freeze drying is performed at -50°C for 10-15h.
[0019] The present invention also provides an amino-modified graphene oxide adsorption material for efficiently treating hexavalent chromium, which is obtained by the preparation method of the amino-modified graphene oxide adsorption material for efficiently treating hexavalent chromium.
[0020] The present invention also provides an application of an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium in removing hexavalent chromium ions from water. The present invention has the following beneficial effects:
[0021] 1. The raw materials in the preparation method of the present invention are easily available and low in cost, which is conducive to large-scale application. In addition, the GO / ATA adsorption material is made of environmentally friendly and non-toxic raw materials, and no harmful substances are released during use, which meets safety and environmental protection standards.
[0022] 2. The GO / ATA adsorbent material of the present invention exhibits extremely high Cr(VI) adsorption capacity, which is superior to other existing adsorbents.
[0023] 3. The covalently cross-linked GO / ATA adsorption material of the present invention has excellent chemical stability and is not easily affected by environmental conditions such as temperature and humidity, thus ensuring the stability of adsorption performance. It can also be recycled, reducing waste generation and environmental pollution.
[0024] 4. The GO / ATA adsorption material of the present invention can be used as an efficient and economical tool to treat wastewater containing Cr(VI), thereby reducing the harm of Cr(VI) to the environment and public health. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The graph shows the results of the Cr(VI) adsorption performance of GO / ATA adsorption material at different pH values;
[0026] Figure 2 The graph shows the results of the determination of Cr(VI) adsorption performance at different addition amounts of GO / ATA adsorption materials;
[0027] Figure 3 The graph shows the results of the Cr(VI) adsorption performance measurement of GO / ATA adsorption material at different initial Cr(VI) concentrations;
[0028] Figure 4 The graph shows the results of the Cr(VI) adsorption performance measurement of GO / ATA adsorption materials at different adsorption times;
[0029] Figure 5 This is a graph showing the recycling test results of GO / ATA adsorption materials;
[0030] Figure 6 This is the test result diagram of the application of GO / ATA adsorption material in simulated polluted surface runoff. DETAILED DESCRIPTION
[0031] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0032] Example 1
[0033] An amino-modified graphene oxide adsorption material (GO / ATA) for efficiently treating hexavalent chromium, wherein the preparation method thereof comprises the following steps:
[0034] (1) Add 0.58 g of 4-amino-3-azino-5-mercapto-1,2,4-triazole and 0.58 g of terephthalaldehyde to 150 mL of dimethyl sulfoxide, stir and mix evenly, then add 3 mL of 50% 3-aminopropyltriethoxysilane ethanol solution and stir to react at 60° C. for 12 h, then cool, filter and wash in sequence, and dry at 80° C. for 12 h to obtain ATA;
[0035] (2) dissolving the ATA obtained in step (1) in dimethyl sulfoxide at a mass volume ratio of 1:1 to obtain an ATA solution;
[0036] (3) Disperse 0.2 g of graphene oxide in 30 mL of water, add 10 mL of the ATA solution obtained in step (2), stir overnight at 25° C. after ultrasonic treatment, filter and wash, and then freeze-dry at -50° C. in vacuum for 12 h to obtain an amino-modified graphene oxide adsorbent material (GO / ATA) that is efficient in treating hexavalent chromium.
[0037] Example 2
[0038] An amino-modified graphene oxide adsorption material for efficiently treating hexavalent chromium, the preparation method of which comprises the following steps:
[0039] (1) 0.4 g of 4-amino-3-azino-5-mercapto-1,2,4-triazole and 0.4 g of terephthalaldehyde were added to 150 mL of dimethyl sulfoxide, stirred and mixed evenly, and then 3 mL of 50% 3-aminopropyltriethoxysilane ethanol solution was added and stirred for reaction at 50° C. for 10 h, and then cooled, filtered and washed in sequence, and dried at 70° C. for 10 h to obtain ATA;
[0040] (2) dissolving the ATA obtained in step (1) in dimethyl sulfoxide at a mass volume ratio of 1:1 to obtain an ATA solution;
[0041] (3) Dispersing 0.1 g of graphene oxide in 20 mL of water, adding 8 mL of the ATA solution obtained in step (2), stirring at 25° C. overnight after ultrasonic treatment, filtering and washing, and vacuum freeze-drying at -50° C. for 10 h to obtain an amino-modified graphene oxide adsorbent material that is efficient in treating hexavalent chromium.
[0042] Example 3
[0043] An amino-modified graphene oxide adsorption material for efficiently treating hexavalent chromium, the preparation method of which comprises the following steps:
[0044] (1) 0.7 g of 4-amino-3-azino-5-mercapto-1,2,4-triazole and 0.7 g of terephthalaldehyde were added to 150 mL of dimethyl sulfoxide, stirred and mixed evenly, and then 3 mL of 50% 3-aminopropyltriethoxysilane ethanol solution was added and stirred for reaction at 70° C. for 15 h, and then cooled, filtered and washed in sequence, and dried at 90° C. for 15 h to obtain ATA;
[0045] (2) dissolving the ATA obtained in step (1) in dimethyl sulfoxide at a mass volume ratio of 1:1 to obtain an ATA solution;
[0046] (3) 0.3 g of graphene oxide was dispersed in 40 mL of water, 12 mL of the ATA solution obtained in step (2) was added, and the mixture was stirred at 25° C. overnight after ultrasonic treatment. After filtering and washing, the mixture was vacuum freeze-dried at −50° C. for 15 h to obtain an amino-modified graphene oxide adsorbent material that is efficient in treating hexavalent chromium.
[0047] Test Example 1 Determination of the adsorption performance of Cr(VI) under different environments
[0048] (1) Determination of Cr(VI) adsorption performance of GO / ATA adsorbent materials at different pH values
[0049] Take 7 portions of 50mL of 500mg / L Cr(VI) mother solution in a conical flask, add deionized water to dilute it to 80mg / L, use 0.1M HCl and NaOH solution to adjust the pH value to 1, 2, 3, 4, 5, 6 and 7 respectively, then add 50mg of GO / ATA adsorbent material of Example 1, and oscillate at constant temperature for 12h at 25℃ and 130rpm. After the reaction is completed, filter and collect the filtrate, and measure the concentration change of Cr(VI) by UV-visible spectrophotometer. According to the measured Cr(VI) concentration, calculate the adsorption capacity of GO / ATA adsorbent material for Cr(VI) under different pH conditions. The results are as follows: Figure 1 shown.
[0050] Depend on Figure 1It can be seen that when the pH value increases from 1.0 to 7.0, the adsorption capacity decreases significantly. At pH = 2, the adsorption capacity reaches the maximum, which is 146.8 mg / L. The adsorption capacity at pH = 2 is more than 30 mg / g higher than that at pH = 7. This is because at lower pH values, the amino groups on the surface of GO / ATA are more easily protonated and positively charged, while Cr(VI) exists in the form of anions in the solution, which enhances the electrostatic interaction between them and promotes the adsorption of Cr(VI). As the pH value increases, the positive charge on the surface of GO / ATA decreases, weakening the electrostatic interaction with Cr(VI).
[0051] (2) Determination of the effect of different GO / ATA adsorption material addition amounts on Cr(VI) adsorption performance
[0052] Take 5 portions of 50mL 500mg / L Cr(VI) mother solution in a conical flask and dilute to 80mg / L, adjust the pH to 2, add 25mg, 40mg, 50mg, 60mg and 75mg of the GO / ATA adsorbent material of Example 1, respectively, and oscillate at a constant temperature of 25°C and 130rpm for 12h. After the reaction is completed, the filtrate is collected by filtration, and the concentration change of Cr(VI) is measured by UV-visible spectrophotometer, and the adsorption capacity under different GO / ATA addition amounts is calculated. The results are as follows: Figure 2 shown.
[0053] Depend on Figure 2 It can be seen that when the dosage of GO / ATA increases from 0.5g / L to 1.0g / L, the adsorption capacity increases sharply from 113.2mg / g to 147.8mg / g. This enhancement is due to the increased availability of functional groups and active sites in the solution, which promotes greater interaction between the GO / ATA adsorbent material and Cr(VI) ions; however, as the dosage of GO / ATA further increases to 1.2g / L and 1.5g / L, the adsorption capacity gradually begins to decrease. This decrease may be due to the fact that excess GO / ATA will aggregate in the solution, which is not conducive to the contact between active sites and Cr(VI) ions, resulting in a decrease in adsorption capacity.
[0054] (3) Determination of Cr(VI) adsorption performance of GO / ATA adsorbent materials at different initial Cr(VI) concentrations
[0055] Cr(VI) solutions with initial concentrations of 40 mg / L, 60 mg / L, 80 mg / L and 100 mg / L were prepared respectively, 50 mL of each solution was taken in a conical flask, the pH value was adjusted to 2, and then 50 mg of the GO / ATA adsorbent material of Example 1 was added, and constant temperature oscillation was performed at 25°C and 130 rpm for 12 h. After the reaction was completed, the filtrate was collected by filtration, and the residual concentration of Cr(VI) in each sample was determined using a UV-visible spectrophotometer, and the adsorption capacity was calculated. The results are shown in FIG. Figure 3 shown.
[0056] Depend on Figure 3 It can be seen that when the initial Cr(VI) concentration increased from 40 mg / L to 100 mg / L, the adsorption capacity of GO / ATA for Cr(VI) gradually increased from 71.23 mg / g to 159.6 mg / g. This is because the higher initial Cr(VI) concentration provided a stronger mass transfer driving force, which promoted the adsorption of Cr(VI) on the active sites of GO / ATA, thereby enhancing the adsorption process.
[0057] (4) Determination of Cr(VI) adsorption performance of GO / ATA adsorbent material at different adsorption times
[0058] A Cr(VI) solution with a concentration of 80 mg / L was prepared, 50 mL of the solution was taken into multiple conical flasks and the pH value was adjusted to 2, then 50 mg of the GO / ATA adsorbent material of Example 1 was added respectively, and the mixture was placed in a constant temperature oscillator at 25°C and oscillated at a speed of 130 rpm for 5 min, 15 min, 30 min, 60 min, 120 min, 180 min, 240 min, 300 min, 360 min, 480 min, 720 min, 1080 min and 1440 min, respectively. At each specified time point, the oscillation was stopped and the filtrate was immediately collected by filtration. Finally, the residual concentration of Cr(VI) in each sample was determined using a UV-visible spectrophotometer, and the adsorption capacity was calculated. The results are shown in FIG. Figure 4 shown.
[0059] Depend on Figure 4 It can be seen that within the first 240 minutes, the adsorption capacity of GO / ATA for Cr(VI) increased rapidly and eventually reached equilibrium, with an equilibrium adsorption capacity of 157.4 mg / g. In the early stage of adsorption, due to the large number of active groups available for adsorption on the surface of GO / ATA, a high adsorption rate was shown. As time went on, the active sites were gradually occupied, adsorption became more difficult, and equilibrium was finally reached.
[0060] Test Example 2 GO / ATA Recycling Test
[0061] Take 50mL of 500mg / L Cr(VI) mother liquor in a 200mL conical flask and dilute to 80mg / L, adjust the pH value to 2, then add 50mg of the GO / ATA adsorption material of Example 1, and oscillate at a constant temperature of 25°C and 130rpm for 12h. After the reaction is completed, filter and collect the filtrate and use a UV-visible spectrophotometer to determine the residual concentration of Cr(VI) to calculate the adsorption efficiency. After completing an adsorption experiment, filter the GO / ATA, immerse it in a 0.1M NaOH solution, ultrasonically treat it for 30min, then rinse it with deionized water, air-dry it and reuse it, repeat the adsorption test, and determine the adsorption efficiency of Cr(VI) after each cycle. The results are as follows: Figure 5 shown.
[0062] Depend on Figure 5 It can be seen that after 5 adsorption-desorption cycles, the removal rate dropped from 91.2% to 72.7%, which shows that the GO / ATA adsorbent has good stability and reusability. Even after multiple adsorption-desorption cycles, its adsorption effect remains at a high level. There are two reasons for the decrease in Cr(VI) removal rate: GO / ATA mass loss during continuous washing; and the sulfur groups in GO / ATA are gradually oxidized during the adsorption process.
[0063] Test Example 3 Application of GO / ATA in Simulating Polluted Surface Runoff
[0064] The field water sample was collected from the runoff near a municipal concrete road (30.8°N, 104.2°E). After the field water sample was left to stand for 2 hours, 50 mL of the supernatant was carefully aspirated. In order to simulate the actual situation of the wastewater, K2Cr2O7 was added to the supernatant to make the initial concentration of Cr(VI) reach 249.3 mg / L. The GO / ATA adsorption material of Example 1 was used to remove Cr(VI) from the simulated polluted water. The concentration of Cr(VI) in the prepared wastewater was determined by a UV-visible spectrophotometer, and the adsorption efficiency was calculated. The results are shown in Figure 1. Figure 6 shown.
[0065] Depend on Figure 6 It can be seen that with the increase of GO / ATA dosage, the adsorption efficiency of Cr(VI) in runoff gradually increased. At a dosage of 3 g / L, the adsorption efficiency of Cr(VI) was 94.9%.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium, characterized in that: The following steps are involved: (1) adding 4-amino-3-azino-5-mercapto-1,2,4-triazole and terephthalaldehyde to dimethyl sulfoxide, stirring and mixing, then adding 3-aminopropyltriethoxysilane ethanol solution and stirring to react, and then cooling, filtering, washing and drying in sequence to obtain ATA; (2) dissolving the ATA obtained in step (1) in dimethyl sulfoxide to obtain an ATA solution; (3) dispersing graphene oxide in water, adding the ATA solution obtained in step (2), stirring overnight after ultrasonic treatment, and then filtering, washing and vacuum freeze-drying in sequence to obtain an amino-modified graphene oxide adsorbent material that is efficient in treating hexavalent chromium.
2. The method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 1, characterized in that: In step (1), the 3-aminopropyltriethoxysilane ethanol solution is prepared by mixing 3-aminopropyltriethoxysilane and ethanol in a ratio of 1:
1.
3. The method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 1, characterized in that: In step (1), the mass volume ratio of the 4-amino-3-azino-5-mercapto-1,2,4-triazole, terephthalaldehyde, dimethyl sulfoxide and 3-aminopropyltriethoxysilane ethanol solution is 0.4-0.7 g: 0.4-0.7 g: 120-180 mL: 2-4 mL.
4. The method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 1, characterized in that: In step (1), the reaction is stirred at 50-70° C. for 10-15 h.
5. The method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 1, characterized in that: In step (1), drying is performed at 70-90° C. for 10-15 hours.
6. The method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 1, characterized in that: In step (2), the mass volume ratio of ATA and dimethyl sulfoxide is 1:
1.
7. The method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 1, characterized in that: In step (3), the mass volume ratio of the graphene oxide, water and ATA solution is 0.1-0.3 g: 20-40 mL: 8-12 mL.
8. The method for preparing an amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 1, characterized in that: In step (3), vacuum freeze drying is performed at -50°C for 10-15h.
9. The amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium obtained by the preparation method of the amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to any one of claims 1 to 8.
10. Use of the amino-modified graphene oxide adsorbent material for efficiently treating hexavalent chromium according to claim 9 in removing hexavalent chromium ions from water.